VIEW ON HEALTH CARE SYSTEM OF THE REPUBLIC OF SERBIA - Anđelić, Slavica; Vidanović, Vojin; Milutinović, , Olivera (Annals of Nursing, 2024)
Background and aim: From the viewpoint of the theoretical description of the healthcare system management, it is significant to identify and evaluate the effects of the organization, financing, and rationalization of the healthcare system of the Republic of Serbia. In its practical application, it is related to the strategic decision-making process for improving functions and developing necessary and proper changes within the same system. It also relates to healthcare human resources, as well as proper client satisfaction and education. Conclusion The health care system has characteristics that distinguish it from other areas. The globalization of the market and the growing needs of society require the healthcare system to be organized in such a way as to meet all the demands of patients and to guarantee their satisfaction. User satisfaction is ensured by achieving the highest possible quality in disease diagnosis, treatment, and patient care at acceptable prices and with as little risk of errors and adverse effects concerning patients as possible.